Emissões de gases de efeito estufa no sistema interligado nacional metodologia para definição da linha de base e avaliação do potencial de redução das emissões do PROINFA - Reis, Tereza Virgínia Mousinho (2002)
The principal motivation of this proposal arose as a result of the decisions adopted at the Accord of Marrakech, COP 7, admitting the application of simplified modalities and procedures to small scale projects, associated to determined categories and types of projects. The current dissertation has as objective to define annual baselines to the National Interconnected System (SIN) and its subsystems, expressed in tCO/GWh, and to assess the potential to emissions reduction due to activities of small projects qualified within the scope of the National Program of Incentives to Alternative Energy Sources (PROINFA). The methodology used to define the values of baselines internalizes to the calculation process the mid term planning to the operation of SIN and the expansion program of the electric sector, formalized in the Ten Years Expansion Plan (PDE) 2001/2010 . It adopts, to calculate the value of the emissions reduced, the calculation method denominated hybrid of the weighed average and build margin . The baselines determined with the use of this method, expressed in tCO /GWh, are represented by the Emissions Standard Factors (FPEs). The total emissions, tCO /year, are seen as baselines in absolute terms, determined by the configuration that doesn t consider the information of activity of projects that mitigates greenhouse effects, foreseen to operate integrated to SIN. The FPEs to SIN and its subsystems are calculated by the weighed average method, to the period between 2001 and 2005, resulting from the multiplication of the average Carbon Emission Factor (FEC) for each type of fuel defined to the Brazilian electric sector, for the participation, per type of fuel, of the conventional thermal generation foreseen until 2005 (see table 4.5), determined based on the results of the simulations of Newave to the Monthly Operation Program (PMO) of April 2002. Due to this fact, they are applied only to the sum of the energy to be supplied, each year, by small projects, suposedly mitigators of GEEs, if not superior to 5% of the total annual energy supplied by SIN. This percentage corresponds, approximately, to the historical value of energy supplied by the conventional thermal plants, delivered by the National System Operator (ONS). The second approach, based on the concept of build margin, is used to establish the FPEs between 2006 and 2007, last year of the range of the study. The building of the margin requires the definition of a Carbon Emission Factor (FEC) and of a composition structure to energy sources, or the mix, that, probably, will represent the profile of generation of the system, by the end of the study. In the present dissertation a emission reference factor in 2027 has been defined, corresponding to the most advanced technology available actually in developed countries to natural gas with combined cycle that, according to Bernow , associates emissions of 359tCO /Gwh. The result found showed that the establishment of annual baselines standardized to the SIN allows, with much simplicity and trustfully, to elaborate projections on the evolution of total emissions to the electric sector or to determined regions of the country, and to assess the potential of reduction of those emissions, as a consequence to the implementation of policies and/or programs mitigating of those emissions. It became evident, nevertheless, that the results are trustable for a maximum period of ten years. Due to the uncertainties associated to the expansion plans of the national electric sector, the results found after the tenth year must be seen only as a indicative, needing that new hypothesis to be formulated to the long term. In the comparison of the values found in two other studies that estimated the total emissions results found in SIN, tCO /year, adopting different methodologies, it has been observed that the the present dissertation, although smaller, didnÌt present expressive differences, at least to one of the alternatives of total emissions considered in this study. The magnitude of the impacts that the small projects implemented within PROINFA can cause in terms of SINÌs GEEs emissions reduction will depend of the percentage of energy supplied by these projects and how much of this energy will dislocate, effectively, the annual generation of conventional thermal plants. However, considering the hipothesys of this dissertation on the behavior of the conventional thermal generation, it is verified that the reduction of the emissions of the SIN due to the activity of the projects to be implemented by PROINFA, during the period of the study, will have expressive impacts. It wasnÌt possible to establish how the benefic potentials, in terms of reduction of the emissions of SIN can be converted into certified reduced emissions (ERCs) within CDM, since these results will depend of the behavior and the evolution of the international carbon market, of the eligibility criteria that will be adopted in Brazil and of how the country can be inserted competitively in this market.